The Effect of Short-Term Auditory Training on Speech in Noise Perception and Cortical Auditory Evoked Potentials in Adults with Cochlear Implants - Barlow, Nathan; Purdy, Suzanne C.; Sharma, Mridula; Giles, Ellen; Narne, Vijay (Seminars in Hearing, 2016)
This study investigated whether a short intensive psychophysical auditory training program is associated with speech perception benefits and changes in cortical auditory evoked potentials (CAEPs) in adult cochlear implant (CI) users. Ten adult implant recipients trained approximately 7 hours on psychophysical tasks (Gap-in-Noise Detection, Frequency Discrimination, Spectral Rippled Noise [SRN], Iterated Rippled Noise, Temporal Modulation). Speech performance was assessed before and after training using Lexical Neighborhood Test (LNT) words in quiet and in eight-speaker babble. CAEPs evoked by a natural speech stimulus /baba/ with varying syllable stress were assessed pre- and post-training, in quiet and in noise. SRN psychophysical thresholds showed a significant improvement (78% on average) over the training period, but performance on other psychophysical tasks did not change. LNT scores in noise improved significantly post-training by 11% on average compared with three pretraining baseline measures. N1P2 amplitude changed post-training for /baba/ in quiet (p = 0.005, visit 3 pretraining versus visit 4 post-training). CAEP changes did not correlate with behavioral measures. CI recipients' clinical records indicated a plateau in speech perception performance prior to participation in the study. A short period of intensive psychophysical training produced small but significant gains in speech perception in noise and spectral discrimination ability. There remain questions about the most appropriate type of training and the duration or dosage of training that provides the most robust outcomes for adults with CIs.
Keywords: Cochlear implant; cortical auditory evoked potential; auditory rehabilitation; auditory training; auditory plasticity; speech in noise